Gastos com bens duráveis no ciclo da vida das famílias Brasileiras - Marcos Antonio Coutinho da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Understand the evolution of the size and allocation of household savings throughout the life cycle is of fundamental importance in the design of public policies. In this sense, durable goods expenditure cannot be ignored as it is an important form of savings with significant participation in personal budget. In addition, credit market imperfections make interdependent the allocative decisions among durable goods, non-durable goods and financial assets. With this motivation, the work uses data from the Consumer Ex penditure Survey from 2008-2209 to describe and analyze the evolution throughout the life cycle of the durable goods expenditure of Brazilian families. The data reveal a behavior compatible with the hypothesis that families prefer to buy at an early stage of the cycle all the desired stock of durable goods, in order to smooth consumption of their services over time. However, the existence of credit constraints, mainly for the financing of goods with higher unit value, prevents spending on durable goods follow their optimal trajectory.
Keywords: E21; 330; durable goods; life cycle; consumption; saving